PENGARUH SAFETY LEADERSHIP DAN SAFETY CLIMATE PADA SAFETY BEHAVIOUR - YOPPI SYAHRIAL (STIE Atma Bhakti, 2017)
This study examines the effect of safety leadership and safety climate on safety behavior . The samples in this study were employees of PT Bentoel International Investama in Surakarta . As for the respondents in this study were employees engaged in work activities in the company and can provide the information needed in the study and be willing to be the respondent . This survey respondents totaled 126 respondents of 150 employees . The sampling method used was nonprobability sampling , whereas the technique used was convenience sampling . Analysis of data using multiple regression analysis . Based on the analysis of the results obtained : 1 ) safety leadership have influence on safety behavior , 2) safety climate has an influence on safety behavior . Advice can be given to the company is the company must maintain and increase safety leadership and safety climate within the company . Due to a leader who has the attitude motivating , thoughtful , and pay attention to the safety of employees as well as the atmosphere of safety will be able to influence the behavior of employees safety . This will create a positive climate within the company that will ultimately reduce the incidence of workplace accidents , improve employee performance and automatically will also benefit the company . Keywords: safety leadership, safety climate, safety behaviour.